Maan viljavuustekijäin keskinäiset vuorosuhteet maalajeittain - Lakanen, Esko; Sillanpää, Mikko; Kurki, Martti; Hyvärinen, Seppo (Agricultural and Food Science, 1970)
The interrelations of pH, exchangeable calcium, potassium and readily soluble phosphorus were studied with the aid of a computer from a total of about 80 000 soil samples. The results showed that soil type has a very pronounced effect on the amounts and behaviour of fertility factors (pH, Ca, K, P). In spite of the levelling effect of liming and fertilization, the differences between various soil types are still visible (Figures 1—4). Exchangeable calcium and soil pH, both of which factors reflect the liming status of acid Finnish soils, are also the most important factors affecting the solubility and plant availability of phosphates. The amount of exchangeable potassium depends again on the soil type, but the effects of potassium and phosphorus on the other fertility factors are negligible when compared with those of soil type, calcium and pH. The increase of the soil pH due to liming decreases with decreasing particle size and increasing organic matter content in the following order: moraine and sand soils, finesand soils, silt, clay soils, mould, mud soils, peats. The beneficial effect of liming on the amount of readily soluble phosphorus decreases in the same order. Soil pH, however, is the critical factor regulating the amount of readily soluble phosphorus, which remains rather low in acid soil up to pH 6. From pH 6 to 7, the solubility of phosphorus increases several times (Fig. 2 C). Contrary to general belief, liming of acid organogenic soils gives rise to a slight decrease in the solubility of phosphorus. The minimum solubility (P 3.5—4.0 mg/l of soil) occurs near pH 5.5.